Tales from a not-so-best friend forever - Russell, Rachel Renée; Russell, Nikki (Russell, Rachel Renée. Dork diaries, 2019)
Nikki and her friends are looking forward to an amazing summer as the opening act for the incredibly popular Bad Boyz on their concert tour. But when Mackenzie manages to land the position of social media intern for the tour and becomes Nikki's roommate, the summer quickly takes a turn towards awful.